Pembangunan Website Company Profile Sebagai Media Promosi Digital Pada Pt. Mitra Makmur Global - Juliansyah, Ferro Luis; Elsi, Zulhipni Reno Saputra; Karnadi, Karnadi (LPPM Institut Pendidikan Nusantara Global, 2025)
The development of information technology has driven major changes in corporate promotion and communication strategies, one of which is through the use of company profile websites. This study aims to design and implement a web-based company profile website for PT Mitra Makmur Global; a company engaged in the heavy equipment rental sector. The research method used is a qualitative method with a Waterfall system development model, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The website is designed to provide information about the company profile, vision and mission, services, and contacts in an interactive and easily accessible manner. The implementation results show that the company profile website is able to improve the company's professional image, expand the reach of promotions, and make it easier for potential clients to obtain information related to the company's services. In addition, the implementation of a responsive interface design and structured navigation makes users feel more comfortable in navigating the site. In conclusion, the development of the PT Mitra Makmur Global company profile website plays a significant role in strengthening the company's digital presence, increasing customer trust, and becoming an effective promotional tool in the digital era.